The effect of carbohydrate states on resistance exercise performance - Di Lauro, P. C.; Mitchell, J. B.; Pizza, F. X.; Lambert, C. P.; Cavender, D. L. (Medicine & Science in Sports & Exercise, 1996)
The effects of high and low pre-exercise carbohydrate (CHO) diet on performance and metabolic responses during multiple sets of resistance exercises were analyzed. CHO status did not affect resistance exercise performance. There was an increased reliance on blood glucose to fuel performance when pre-exercise CHO status was low. Implication. CHO status is not a critical factor for resistance exercise performance. However, when multiple training sessions, recovery times, and other forms of training are important, CHO levels should be maintained at their highest levels.